2019
DOI: 10.1155/2019/4012450
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cereal Products in the Diet for Type 2 Diabetes Patients

Abstract: Type 2 diabetes has become one of the major health problems of the modern world. It is assumed that environmental factors have a significant impact on the development of the disease, and great importance is ascribed to the diet, which can be modified accordingly. The diet can exert prophylactic and therapeutic effects; changes in the diet in advanced disease can improve the quality of life of diabetic patients and minimise the risk of complications, which are the direct cause of diabetes-related death. Functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 71 publications
0
16
0
1
Order By: Relevance
“…Krawecka et al, also reported that Dietary fibre as a group of compounds comprising plant polysaccharides, oligosaccharides, lignins, fructans and β-glucans does not increase the level of glycaemia and also reported that cereal grains are rich mainly in the insoluble fraction of dietary fibre, and the greatest amount of fibres are found in wholegrain milled products and that higher consumption of such products is associated with reduction of the type 2 diabetes risk in subjects with glucose intolerance. They also indicated that the glyceamic response of bread appears to be lower after the incorporation of whole or cracked rye or barley grains [20].…”
Section: Results Of Functional Propertiesmentioning
confidence: 99%
“…Krawecka et al, also reported that Dietary fibre as a group of compounds comprising plant polysaccharides, oligosaccharides, lignins, fructans and β-glucans does not increase the level of glycaemia and also reported that cereal grains are rich mainly in the insoluble fraction of dietary fibre, and the greatest amount of fibres are found in wholegrain milled products and that higher consumption of such products is associated with reduction of the type 2 diabetes risk in subjects with glucose intolerance. They also indicated that the glyceamic response of bread appears to be lower after the incorporation of whole or cracked rye or barley grains [20].…”
Section: Results Of Functional Propertiesmentioning
confidence: 99%
“…These acids absorbed by colonocytes through the portal vein entered the liver, where they regulated the metabolism of fatty acids and cholesterol. Propionic acid was of particular importance, as it inhibited the synthesis of fatty acids that reached the bloodstream and regulated adipocytokines (adipokines), i.e., proteins responsible for inter alia , glycemic homeostasis, and lipidemia [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is still an upward trend in the incidence of type 2 diabetes and cardiovascular diseases [ 6 , 7 ]. An integral part of preventing these diseases is to increase dietary fiber intake [ 8 , 9 , 10 ]. Several studies have emphasized that high consumption of cereal-derived fiber is associated with a reduction in the risk of development of type 2 diabetes [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extruded pasta produced with durum semolina is characterized by a low glycemic index. The unique structure of pasta, in which starch is tightly surrounded by a protein matrix, hinders the activity of amylolytic enzymes and thus slows down the dynamics of glucose release and reduces postprandial glycemia [6]. In addition, pasta is a food product that can be easily fortified with plant raw materials rich in phytochemicals with hypoglycemic, antioxidant, or hypocholesterolemic effects.…”
Section: Introductionmentioning
confidence: 99%